Seed fall and leaf litter relationships in Nothofagus pumilio forests: changes according to retention levels and years after harvesting - Rodríguez‑Souilla, Julián (2023)
Seed fall and leaf litter influence forest regeneration, nutrient cycling, and other key ecological processes closely related to forest management. In Patagonian forests, variation of both managed and unmanaged forests over the years can influence their resilience, where the sustainability implications of harvesting are not fully understood. The aim was to analyse the relationship between seed fall and leaf litter in variable retention harvesting and unmanaged Nothofagus pumilio forests in the medium term. Seed production (S) and leaf litter (LL) in primary unmanaged forests and three retention types were measured over the years after harvesting (YAH). Two indexes (SI, LLI) were calculated based on basal area for both S and LL. Due to harvesting, forest structure varied between retention levels. Both seed production and leaf litter decreased in managed forests, but statistical differences were not found when comparing SI. In addition, LLI was higher in the harvested areas. Forest harvesting progressively showed an increase in LLI values over the YAH, but SI maintained similar values. For all forest types, LLI presented higher values for years with low SI, and this could be linked with a source–sink limitation relationship. Finally, managed forests provide higher values of LLI for similar values of SI, contributed mainly by unmanaged areas. Seed fall and leaf litter production evidenced alterations in the medium term after harvesting. These findings have important implications for the adjustment of forest management practices, and for the understanding of the regulation and support of ecosystem service provision.